The Association of Foot Care Strategies (FCS) through Ablution with Hba1c among Diabetes Mellitus Type 2 Patient - Majin, Rosnah; Musa, Mazlinda; Hassan, Hamidah; Mamat, Rohani; Noh, Malehah Mohd (Indonesian Journal of Global Health Research, 2023)
Diabetes Mellitus in Malaysia has become increasingly problematic along with issues of other cardiovascular conditions such as hypertension, heart disease and stroke. Therefore, the aim of this study is to determine the association of Foot care strategies (FCS) through ablution with Hba1c result among Diabetes Mellitus Type 2. The study design used is a Quasi experimental design. The intervention group received an Educational Package that focused on ablution, while the control group did not receive any form of intervention and received standard health care. A Wilcoxon test was used for the statistical analyses. There are no statistical changes in the mean difference of score in intervention and control group after implementation of Diabetic Foot Care Strategies for intervention group Pre-test (M=7.706, SD=2.598, P 1.000) and Post-test is (M=7.706, SD (2.598), P 1.000). It was found that 0% Changes from baseline to post test. In this study has found that there was no effect between the improvement of foot hygiene with Hba1c result even though respondent Hba1c result were well control and poorly control.